Patient Safety Culture at Rumah Sakit Mata Undaan in 2023: An HSOPSC Survey - Kartika Sari, Dyan; Nurharianti, Pradita Rani; Asih, Akas Yekti Pulih (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2025)
The cornerstone of patient safety is a culture of safety, which can significantly reduce adverse events. According to the 2022 Hospital Accreditation Standards, hospitals are required to measure and evaluate patient safety culture annually. This research aims to assess the level of patient safety culture at Rumah Sakit Mata Undaan so it can serve as a reference for developing policies to enhance patient safety culture. This study employs a cross-sectional design and a quantitative methodology to conduct a descriptive investigation. This study includes the entire population, with a total sample size of 189 respondents, consisting of non-health workers, medical staff, and other healthcare workers. Measurement was conducted using the ten safety culture variables from the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire developed by AHRQ. The result indicate that  69.4% of respondents, on average,  agreed with the patient safety culture dimensions. Among them, "Teamwork" received the highest percentage of favorable responses (86%), while "Communication Openness" had the lowest percentage  (55%). Overall, the patient safety culture at Rumah Sakit Mata Undaan in Surabaya falls into the "Moderate" category. Improvements are needed to strengthen safety dimensions that are currently in the  moderate category, aiming to elevate them to the strong category. Keywords: hospital, patient safety culture, HSOPSC, AHRQ